Investigation of an active mixer - Khoo, Shinvy. (2010)
Every few years a new disease seems to have everyone in the throes of its wake. In 1997 it was bird flu; recently the swine flu swelled to a global pandemic, with these viral diseases running amok, it is obvious that there are increasing number of new viruses and bacteria are to be found or spot.